Modified biophysical profile in high-risk pregnancy-association with neonatal APGAR score - Asgari Begum, Vemala; Sruthi, Reddygari; Sai Mamatha, Sanikommu Venkata; Kameshwaramma, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: MBPP is used for evaluating fetal health and predicting fetal outcomes, which can help to minimize perinatal morbidity and death. It combines the non-stress test, an indicator of acute fetal hypoxia, with AFI, the second indicator of persistent fetal problems. Each patient has a non-stress test and an ultrasonic examination of liquor volume. A non-stress test that is reactive will reveal a healthy fetus. Hence, an attempt has been made to study the MBPP in high-risk pregnancies in predicting fetal outcome. Methods: Hospital-based prospective clinical study on 200 high-risk pregnant women more than 37weeks of gestation are screened using a modified biophysical profile. High-risk factors in the study include Gestational Hypertension, Preeclampsia, IUGR, Post-term pregnancy, Oligohydramnios, PROM, and Anemia. The study was conducted in the department of obstetrics and gynaecology, Narayana medical college and hospital, Nellore, Andhra Pradesh. Results: In the present study, a total of 200 patients, 76.0% had both (NST, AFI) normal, 5.0% had both (NST, AFI) abnormal, 10.0% had Normal in NST and abnormal in AFI, 9.0% had abnormal in NST, and normal in AFI. The individual association between NST and AFI with the neonatal outcomes ie., APGAR at 1 min and 5min have been studied and have been found to be statistically significant. Conclusions: In the present study, we concluded that MBPP is an effective antepartum fetal surveillance test in high-risk pregnancies in predicting perinatal outcome.